Probing the deformation mechanisms of AlCoCrFeNi alloy at various strain rates and grain sizes - Tan, Jaz Whee (Nanyang Technological University, 2022)
This study probes on the deformation mechanisms present in nano crystalline AlCoCrFeNi high-entropy alloy, with uniaxial tension simulations conducted using molecular dynamics simulations. The influence of strain rate and grain size were investigated. Strain rates of 1 x 10^8 /s, 5 x 10^8 /s and 1 x 10^9 /s, and grain sizes 6 nm, 7.5 nm and 10 nm were chosen. The results of stress-strain graphs, deformation mechanisms, microstructure changes and dislocation analysis were discussed. Dislocation slippage due to the formation of stacking faults was observed. As strain increases, partial dislocation emitted from grain boundaries increases. The increase in strain rate results in higher yield stress and a larger percentage of amorphous structures. Inverse Hall-Petch relationship was also observed in the study, along with different formations of stacking faults present and some grain boundary induced mechanisms present at smaller grain sizes (6 nm).